Designing Digital Tools in Fisheries: What Fisherfolks Want in Malawi - Patrick Kawaye Chimseu; Samson Pilanazo Katengeza; Emmanuel Kaunda; Joseph Dzanja; Abigail Bennett (Aquaculture, Fish and Fisheries)
ABSTRACT Use of digital tools is rapidly transforming the world, and Information and Communications Technology (ICT) integration in fisheries presents great opportunities for enhancing fishing‐dependent livelihoods. This article employed latent class analysis and a multinomial logistic regression to explore preferred digital tools for fish traders to address the problem of lack of access to market information. Results from a sample of 548 participants show heterogeneous preferences among fish traders who can be classified into three subgroups: digital‐wise (70%), phone‐wise (24%) and digital‐local (6%) across different platforms and prefer the use of all platforms (USSD, calls, apps, radio and television [TV] programmes). On the basis of platform ranking, traders prefer calls more, followed by app, USSD, radio and TV, respectively. Results further show that social demographic characteristics, including marital status, gender, age and trust among players, influence class membership in different subgroups. To address the diverse needs of traders, there is a need for a free, cross‐platform digital system, call centre/USSD service for convenience, data quality checks, endorsements, the provision of digital credit and stakeholder collaboration to exploit digital fish trade opportunities for Malawi to benefit from the African Continental Free Trade Agreement and not to be left behind in the fourth industrial revolution.